Study on vertical motion reduction of a trimaran based on collaborative controlled appendages. (29th December 2020) - Liu, Zhilin; Zheng, Linhe; Li, Guosheng; Yuan, Shouzheng; Yang, Songbai
In recent years, the trimaran as a novel ship has been greatly developed. The subsequent large vertical motion needs to be studied and resolved. In this article, an experimental study for a trimaran vertical stabilization control is carried out. Three modes including the bare trimaran (the trimaran without appendages, the trimaran with fixed appendages, and the trimaran with controlled appendages) are performed through model tests in a towing tank. The model tests are performed in regular waves. The range of wave period is 2.0–4.0 s, and the speed of the carriage is 2.93 and 6.51 m/s. The results of the three modes show the fixed appendages and the actively controlled appendages are all effective for the vertical motion reduction of the trimaran. Moreover, the controlled appendages are more effective for the vertical stability performance of the trimaran.